Development Of A Volleyball Underwear Passing Training Model For Students - Sahabuddin; Hakim, Hikmad; Ishak, Muhammad; Hasanuddin, M. Imran (Indonesian Journal of Physical Activity, 2024)
The purpose of this research and development is to produce a volleyball underhand passing training model. In addition, research and development are conducted to obtain in-depth information about the development and application of training models and to determine the effectiveness and efficiency of the models created. This research and development uses the Research & Development (R&D) research and development method from Borg and Gall. The subjects in this research and development are students of SMK Negeri 7 Makassar. The effectiveness test of the model uses an underhand passing test instrument to collect data on the abilities of volleyball athletes. The effectiveness test of the model uses an underhand passing test instrument to Test the effectiveness of the model uses an underhand passing test instrument to collect data on the abilities of volleyball athletes. Analysis of research data using the t-test with a significance level of 0.05. Data analysis obtained an average value of the underhand passing training model pretest 4.533 and an average posttest 7.400 standard deviation pretest 1.245 and posttest 3.661. The average of the pretest and posttest underhand passing training model is -2.866 and the standard deviation is 2.030, the t value is -5.467, the significance (2-tailed) is 0.000 with a significance level of 0.05, so H2O is rejected. Based on this information, it can be said that the underhand passing training model in playing modern volleyball that is developed is effective and can improve volleyball playing skills. In conclusion, the development of a training model in volleyball games can be applied effectively and efficiently.